Can a carer (peer) led psychoeducation programme improve mental health carers well-being, reduce burden and enrich empowerment: a service evaluation study. Issue 2 (15th March 2019) - Chiocchi, John; Lamph, Gary; Slevin, Paula; Fisher-Smith, Debra; Sampson, Mark
Abstract : Purpose: Carers of people with mental health problems present with high levels of burden, poor mental well-being and feelings of disempowerment by mental health services. The purpose of this paper is to establish whether providing a psychoeducation skill programme for carers would lead to an improvement of mental well-being, reduce the levels of burden that carers sometimes feel while caring for someone with mental illness and also to increase empowerment. This paper provides a service evaluation study of an innovative carer-led psychoeducational intervention that was undertaken. Design/methodology/approach: This programme was initiated and led by a carer who had experienced a lack of service provision to support carers and families in understanding and caring for a relative with severe and enduring mental health diagnoses. A model of co-production was adopted with the carer who led this initiative working closely with an occupational therapist and consultant psychologist in its development and delivery. Data were collected to measure the impact of the training at five different time points. The measures employed to measure outcomes were the Warwick-Edinburgh Mental Well-being Scale, the Burden Assessment Scale and Family Empowerment Scale. Findings: Results indicated improved well-being, reduced burden and increased family empowerment in carers who completed this peer-led carer initiative psychoeducational programme. Research limitations/implications: This service evaluation study was conducted in a single site and in the site in which it was developed. The carer consultant who led this evaluation and development of the intervention was also the peer worker who delivered the interventions. Hence, the authors are unable to ascertain if the results reported are unique to the individual peer worker. The transferability of this programme and generalisability of the result should therefore be treated with caution and further replication of this model and research is required. This would be beneficial to be conducted in an alternative site from where it was developed, delivered by different facilitators and include a control group. Practical implications: The evidence from this study indicates that carers are able and willing to attend a group psychoeducational programme. A high number of referrals to the programme in a relatively short timeframe indicates that there is significant demand for such a service. The implementation of the programme is relatively straightforward. The key challenges for practical implementation are to have the right carer to lead and deliver the programme and the right support system in place for them (financial and supervision). Co-production also is not without challenges, the peer worker and occupational staff need to ensure that mutually valued and respected working relationship should develop. Originality/value: This is the first evaluation of the impact of a carer-led psychoeducation intervention for carers of people with mental health difficulties in secondary mental health services.